1993
DOI: 10.1007/bf02253536
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of morphine dependence and potentiation of analgesia by chronic co-administration of nifedipine

Abstract: Nifedipine, 5 mg/kg IP, potentiated the morphine-induced analgesia measured in the hot-plate, but not in the tail-flick test. Further experiments were carried out using the hot-plate test only. Pretreatment with nifedipine partially restores the analgesic action of morphine in morphine-tolerant rats. Co-administration of nifedipine with morphine in a chronic experiment did not prevent the loss of morphine efficiency (an increase in latency of 44% was not significant) and did not prevent the debilitating effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Because the latter is regarded as at least a partial model for drug addiction (Roberts et al 1995), the present data suggest that L-type Ca 2ϩ channel blocking agents may be useful in the treatment of drug dependence. This, in fact, corroborates our previous studies demonstrating that morphine administration in the presence of nifedipine and other L-type Ca 2ϩ blockers prevents the ability of naloxone to induce withdrawal syndrome in rats chronically injected with morphine (Antkiewicz- Michaluk et al 1990Michaluk et al , 1993Michaluk et al 1998).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Because the latter is regarded as at least a partial model for drug addiction (Roberts et al 1995), the present data suggest that L-type Ca 2ϩ channel blocking agents may be useful in the treatment of drug dependence. This, in fact, corroborates our previous studies demonstrating that morphine administration in the presence of nifedipine and other L-type Ca 2ϩ blockers prevents the ability of naloxone to induce withdrawal syndrome in rats chronically injected with morphine (Antkiewicz- Michaluk et al 1990Michaluk et al , 1993Michaluk et al 1998).…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated that the increase in L-type Ca 2ϩ channel density is observed in a variety of conditions that produce an increase in responsiveness of rats to dopaminergic stimuli, such as repeated electroconvulsive shock (Antkiewicz- Michaluk et al 1990Michaluk et al , 1994b, morphine abstinence (Antkiewicz- Michaluk et al, 1993Michaluk et al, , 1994a or neuroleptic withdrawal (Mamczarz et al 1994, Antkiewicz-Michaluk et al 1995. Co-administration of nifedipine with those treatments inhibits their propensity to produce of various changes, believed to be of adaptive character.…”
Section: Discussionmentioning
confidence: 99%
“…Both compounds, applied alone or in combination, did not significantly change the quantity of brain cytochrome P450. DISCUSSION L-type calcium channel blockers of the dihydropyridine class, such as nifedipine, nimodipine, amlodipine, have been reported to affect different types of drug dependence and withdrawal, including those to opioides (15), alcohol (16), psychostimulants (10). At the same time they are known to be the substrates of one of the most abundant cytochrome P450 isoenzyme CYP3A that interacts with other substrates of this isoform, including cocaine.…”
Section: Discussionmentioning
confidence: 99%
“…L-type calcium channels have been found to regulate a multitude of neuronal processes including neurotransmitter release, gene expression, mRNA stability, neuronal survival, ischemic-induced axonal injury, synaptic efficacy, and the activity of other ion channels (Lipscombe et al, 2004), but it appears that there may be a different role of L-type calcium channels in different brain regions, especially for the effect on neurotransmitter release (Lipscombe et al, 2004;Li and Bennett, 2003;Wiser et al, 1999;Sabria et al, 1995;Reuter, 1996;Lopez et al, 2001;Bargas et al, 1998). In addition, it was reported that some pathophysiologic stimulus such as stress and psychostimulants could significantly elevate the expression of L-type calcium channels in the cerebral cortex (ntkiewicz-Michaluk et al, 1990(ntkiewicz-Michaluk et al, , 1993(ntkiewicz-Michaluk et al, , 1994a(ntkiewicz-Michaluk et al, , b, 1995Mamczarz et al, 1994Mamczarz et al, , 1999 and this elevation had been proposed to be involved in etiology of a variety of psychiatric disorders such as schizophrenia, morphine abstinence, and neuroleptic withdrawal (ntkiewicz-Michaluk et al, 1994a(ntkiewicz-Michaluk et al, , b, 1997(ntkiewicz-Michaluk et al, , 1995(ntkiewicz-Michaluk et al, , 1993Mamczarz et al, 1994Mamczarz et al, , 1999. Moreover, the glutamate release in the medial prefrontal cortex is also important in etiology of a variety of psychiatric disorders Moghaddam et al, 1997;Moghaddam and Adams, 1998).…”
Section: Discussionmentioning
confidence: 99%